2015
DOI: 10.3390/f6103547
|View full text |Cite
|
Sign up to set email alerts
|

Loblolly Pine Growth Patterns on Reclaimed Mineland: Allometry, Biomass, and Volume

Abstract: Surface lignite coal mines in east Texas are commonly reforested using loblolly pine (Pinus taeda L.) following mining and reclamation activities. Due to the nature of such an extreme disturbance, altered growth patterns, growth rates, and productivity could be expected. We destructively sampled above-and belowground tissue to develop prediction equations specific to these sites. These prediction equations differed statistically from those found in the literature regarding unmined land. At the stand level, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 44 publications
(77 reference statements)
1
11
0
Order By: Relevance
“…Amichev et al (2008) demonstrated that ecosystem C sequestration on mined lands are capable of meeting pre-mining levels. Previously published allometric relationships for loblolly pine trees growing on reclaimed mined lands in the Gulf Coastal Plain showed increased biomass and volume growth over time, with growth rates similar to non-mined lands (Priest et al 2015).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Amichev et al (2008) demonstrated that ecosystem C sequestration on mined lands are capable of meeting pre-mining levels. Previously published allometric relationships for loblolly pine trees growing on reclaimed mined lands in the Gulf Coastal Plain showed increased biomass and volume growth over time, with growth rates similar to non-mined lands (Priest et al 2015).…”
Section: Introductionmentioning
confidence: 86%
“…The study site was located at the Beckville Mine, an active lignite surface mine owned by the Luminant Mining Company, LLC (Luminant). The mine covers 12,000 ha in Rusk and Panola counties, Texas (N32°14′20.7414″, W94°29′44.9262″) (Priest et al 2015). Premining soils consisted of Paleudults (Bowie, Lilbert, Kullit, and Darco series), Hapludults (Kirvin, Cuthbert, Sacul, and Tenaha series), and Udifluvents (Iuka series) (Dolezel 1975).…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…The same procedure was used for harvested seedlings. The following model (Priest et al, 2015) was used to predict above and belowground biomass of all planted seedlings after one growing season:…”
Section: Vegetative Samplingmentioning
confidence: 99%